Oxidized glutathione promotes association between eukaryotic translation elongation factor 1Bγ and Ure2p glutathione transferase from Phanerochaete chrysosporium. (20th November 2020) - Bchini, Raphael; Girardet, Jean‐Michel; Sormani, Rodnay; Gelhaye, Eric; Morel‐Rouhier, Mélanie
Abstract : The eukaryotic translation elongation factor 1Bγ (eEF1Bγ) is an atypical member of the glutathione transferase (GST) superfamily. Contrary to more classical GSTs having a role in toxic compound detoxification, eEF1Bγ is suggested to act as a scaffold protein, anchoring the elongation factor complex EF1B to the endoplasmic reticulum. In this study, we show that eEF1Bγ from the basidiomycete Phanerochaete chrysosporium is fully active as a glutathione transferase in vitro and undergoes conformational changes upon binding of oxidized glutathione. Using real‐time analyses of biomolecular interactions, we show that GSSG allows eEF1Bγ to physically interact with other GSTs from the Ure2p class, opening new perspectives for a better understanding of the role of eEF1Bγ in cellular oxidative stress response. Abstract : The eEF1Bγ subunit of the elongation factor complex EF1 is known to act as a scaffold protein stabilizing the complex. Our data demonstrate additional features: It is active as glutathione transferase in the presence of reduced glutathione (A), it changes conformation upon oxidized glutathione binding (B), and oxidized glutathione promotes the interaction between eEF1Bγ and the glutathione transferase Ure2p (C), suggesting putative redox regulation of the complex formation.